What to Pack? The Semiotics of Be-Longing(s) of Syrian Displaced Women - Suyoufie, Fadia F.; Dagamseh, Abdullah M. (Refuge, 2023)
This qualitative study focuses on a group of 42 Syrian displaced women who live in Irbid, Jordan. The women went through the traumatic experience of forced eviction from their homes as a consequence of the civil war in Syria. The participants responded to a questionnaire about the most important things that they packed and whether the objects affected their coping with displacement. Our discussion of the socio-semiotic implications of the carried items validates our main thesis that the displaced women were empowered by the agency of commitment to the re-creation of home life away from home by solidly grounding it in the “dailiness” of domesticity. Through concept-driven coding, the study defines the pervasive patterns of the participants’ responses to the questions about their carried objects in relation to concepts of identity, home, and memory. The conclusion confirms that the women’s commitment to their roles as mothers and homemakers, along with their religious faith-based awareness of displacement, contributes to their sense of agency and resilience.